2011
DOI: 10.1007/s10029-010-0777-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Permacol™ and Strattice™ for the repair of abdominal wall defects

Abstract: Cross-linked materials may prove more durable in the remodeling process as suggested by the increased thinning and weakening observed in non-cross-linked biomesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 11 publications
1
65
1
2
Order By: Relevance
“…Cross-linking is a chemical step during mesh processing that is felt to render the collagen of the biologic matrix less prone to degradation in vivo by naturally occurring collagenases. 18,19 Studies examining the histologic effects of cross-linking have concluded that in the short term there is delay of cellular infiltration and neovascularization; however, these factors are not impacted substantially in the long term based on cross-linking alone. 19 Strattice must be stored between -8°C and 30°C (room temperature) and has a shelf life of 18 months.…”
Section: Biologic Mesh: Options and Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Cross-linking is a chemical step during mesh processing that is felt to render the collagen of the biologic matrix less prone to degradation in vivo by naturally occurring collagenases. 18,19 Studies examining the histologic effects of cross-linking have concluded that in the short term there is delay of cellular infiltration and neovascularization; however, these factors are not impacted substantially in the long term based on cross-linking alone. 19 Strattice must be stored between -8°C and 30°C (room temperature) and has a shelf life of 18 months.…”
Section: Biologic Mesh: Options and Assessmentmentioning
confidence: 98%
“…It is the removal of each tissue's cellular material that is believed to facilitate durability and resistance to infection and prevent xenogeneic rejection. 18 Interestingly, Permacol is cross-linked (with noncalcifying hexamethylene diisoccyanate), and Strattice is non-crosslinked. Cross-linking is a chemical step during mesh processing that is felt to render the collagen of the biologic matrix less prone to degradation in vivo by naturally occurring collagenases.…”
Section: Biologic Mesh: Options and Assessmentmentioning
confidence: 99%
“…Several studies using in vivo animal models have shown good vascularization and cellular infiltration of matrices used for hernia repair. 9,25,26 However, no benefit was noted with regard to skin graft contraction when porcine matrices were used as dermal replacement in rats. 27 Still, because human skin contraction and scarring are unique and poorly reproducible by animal experimental settings, this model is expedient because of its use of human skin organ cultures and cells.…”
Section: Discussionmentioning
confidence: 93%
“…In terms of biomechanical behavior, some authors [38] argue that crosslinked materials may be more durable during tissue remodeling, as suggested by gradual thinning and weakening noted in the noncrosslinked Strattice beyond 3 months of implant use. However, we observed no differences in thickness in the three biomeshes examined over time until 90 days, and neither was a loss in tensile strength produced.…”
Section: Discussionmentioning
confidence: 99%